2016
DOI: 10.1080/21691401.2016.1203796
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial chitosan/silk sericin 3D porous scaffolds as a wound dressing material

Abstract: Antimicrobial mixed dressings have traditionally been used to minimize bacterial infection of burns and other wounds. This study presents the advancement of biocompatible chitosan/silk sericin (CHT/SS) scaffolds combined with lauric acid (LA) and zinc oxide nanoparticles (nZnO) for the successful wound dressing applications. Antibacterial assay results showed that the diameters of the inhibition zone increased from 2 ± 0.4 to 7 ± 0.1 mm for Escherichia coli, as well as from 2.5 ± 0.2 to 6 ± 0.4 mm for Staphylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(34 citation statements)
references
References 46 publications
(43 reference statements)
0
29
0
Order By: Relevance
“…Development of haemostatic wound dressings that induce rapid blood clotting has been shown to be vital in preventing blood loss (Martin, ). A recent study demonstrated haemostatic activity of SF driven by electrostatic interactions, which induces binding with blood platelets, thus enhancing treatment of full‐thickness wounds (Karahaliloglu, Kilicay, & Denkbas, ). Silk‐based nanofibrous mats showed superior haemostatic activity compared with surgical cotton gauze when examined by quantifying the LDH activity of adhered platelets (Figure b; p ≤ .01).…”
Section: Resultsmentioning
confidence: 99%
“…Development of haemostatic wound dressings that induce rapid blood clotting has been shown to be vital in preventing blood loss (Martin, ). A recent study demonstrated haemostatic activity of SF driven by electrostatic interactions, which induces binding with blood platelets, thus enhancing treatment of full‐thickness wounds (Karahaliloglu, Kilicay, & Denkbas, ). Silk‐based nanofibrous mats showed superior haemostatic activity compared with surgical cotton gauze when examined by quantifying the LDH activity of adhered platelets (Figure b; p ≤ .01).…”
Section: Resultsmentioning
confidence: 99%
“…In the study of Aramwit et al, a sericin-based therapeutic cream formulation improved healing by promoting collagen production and rapid re-epithelialization in rat skin wounds (Aramwit et al, 2009(Aramwit et al, , 2013. Both twodimensional (films) and three-dimensional (scaffolds) sericin matrices, obtained using different blending methods, have been reported for skin tissue repair (Nayak et al, 2012;Lamboni et al, 2015;Karahaliloglu et al, 2017). Therefore, a sericin/CaP biomaterial could significantly accelerate and improves wound healing and soft tissue replacement.…”
Section: Other Applicationsmentioning
confidence: 99%
“…Alginate dressings are produced from the sodium and calcium salts comprising mannuronic and guluronic acid units [201,202], e.g., Sorbsan TM , Kaltostat TM and Algisite TM [200,203]. c. Bioactive wound dressings, which are known for their biocompatibility, biodegradability and nontoxic nature, are the last type of the modern wound dressings [204] and are derived generally from the natural tissues or artificial sources which play the serious role in healing process such as collagen [205], hyaluronic acid [206], chitosan [207,208], alginate and elastin. These materials are used alone or in combination depending on the nature and type of wound.…”
Section: Acellular Porcine or Xe-derma Scaffoldmentioning
confidence: 99%